Diversity of aquatic insects in relation to water quality in stream of Sekayu recreational forest, Terengganu / Wahizatul Afzan, A, Amirrudin, A. and Raja Noor Balqhis, R.S. - A., Wahizatul Afzan; A., Amirrudin; R.S., Raja Noor Balqhis (2006)
A total of 1364 individuals of aquatic insects of 38 families belonging to eight orders had been collected from lower stream (LS), middle stream (MS) and upper stream (US) of Sg. Sekayu in Sekayu Recreation Forest, Hulu Terengganu, Terengganu from 5th to 7th September 2005. There are eight common orders of aquatic insects that had been identified namely Trichoptera (40%), Ephemeroptera (25%), Plecoptera (14%), Odonata (12%), Hemiptera (6%) Coleoptera (1%), Diptera (1%) and Megaloptera (1%) during this study. The most dominant order was Trichoptera and Heptageniidae (Order: Ephemeroptera) was the most abundant family which were found at all sampling site. Water conditions and human activities showed a difference in the distribution and abundance of the orders obtained in the three stations. However, there were no significant differences in the total individuals collected and taxonomic composition of aquatic insects in all three sampling sites (ANOVAindividuals, F2,18,005 = 0,472; ANOVA Taxon, F2,18,0.05 = 0.512). Interestingly, based on the Family Biotic Index (FBI) and Biological Monitoring Work Party (BMWP), all sites demonstrated a good water quality even though two sites were considered as disturbed areas.